2020
DOI: 10.1038/s41598-020-58182-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interaction screen for severe neurodevelopmental disorders reveals a functional link between Ube3a and Mef2 in Drosophila melanogaster

Abstract: neurodevelopmental disorders (nDDs) are clinically and genetically extremely heterogeneous with shared phenotypes often associated with genes from the same networks. Mutations in TCF4, MEF2C, UBE3A, ZEB2 or ATRX cause phenotypically overlapping, syndromic forms of NDDs with severe intellectual disability, epilepsy and microcephaly. To characterize potential functional links between these genes/proteins, we screened for genetic interactions in Drosophila melanogaster. We induced ubiquitous or tissue specific kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“… 124 Neuronal activity can promote the translation of UBE3A through the MEF2 complex. 125 TBR1 is a neuron-specific transcription factor required for activity-dependent Grin2b expression, loss of a copy of which alters the expression of Ntng1 , Cntn2 and Cdh8. 109 , 110 …”
Section: Neurobiological Mechanisms Of Asdmentioning
confidence: 99%
“… 124 Neuronal activity can promote the translation of UBE3A through the MEF2 complex. 125 TBR1 is a neuron-specific transcription factor required for activity-dependent Grin2b expression, loss of a copy of which alters the expression of Ntng1 , Cntn2 and Cdh8. 109 , 110 …”
Section: Neurobiological Mechanisms Of Asdmentioning
confidence: 99%
“…Recently, employing a fly ( Drosophila melanogaster ) as a screening model for gene interactions and by consequent co-immunoprecipitation in human cell lines, Straub et al. reported a specific functional correlation between MEF2C and UBE3A that could eventually lead to the phenotypic overlap between MEF2C -related ID and Angelman syndrome [ 185 ]. Nevertheless, there is still a need for more comprehensive scientific support of UBE3A influencing MEF2C gene in an ubiquitous manner.…”
Section: Mef2c As a Risk Factor For Asdmentioning
confidence: 99%
“…Some of the traits of Angelman syndrome can indeed be found on the autism spectrum, for example poor communication skills, absence of speech, attention deficits, hyperactivity, insomnia, and a deficiency in motor growth and development [183,184]. Recently, employing a fly (Drosophila melanogaster) as a screening model for gene interactions and by consequent co-immunoprecipitation in human cell lines, Straub et al reported a specific functional correlation between MEF2C and UBE3A that could eventually lead to the phenotypic overlap between MEF2C-related ID and Angelman syndrome [185]. Nevertheless, there is still a need for more comprehensive scientific support of UBE3A influencing MEF2C gene in an ubiquitous manner.…”
Section: Mef2c As a Risk Factor For Asdmentioning
confidence: 99%
“…Another group investigated the gene regulatory network in which Ube3a is involved [ 195 ]. Mutations in TCF4, MEF2C, UBE3A, ZEB2 or ATRX cause phenotypically overlapping, syndromic forms of neurodevelopmental disorders with severe intellectual disability, epilepsy and microcephaly.…”
Section: Drosophila Epilepsy Modelsmentioning
confidence: 99%
“…Mutations in TCF4, MEF2C, UBE3A, ZEB2 or ATRX cause phenotypically overlapping, syndromic forms of neurodevelopmental disorders with severe intellectual disability, epilepsy and microcephaly. Global or tissue specific knockdown or overexpression of each single orthologous Drosophila genes, such as Da , Mef2 , Ube3a , Zfh1 and XNP and their pairwise combinations were carried out to examine phenotypes such as lethality, wing and eye morphology, NMJ morphology, bang sensitivity and climbing behavior and then compared between single and pairwise dosage manipulations [ 195 ]. By these analyses, genetic interaction between Ube3a and Mef2 via simultaneous dosage manipulation in tissues, such as glia, wing and eye, resulted in multiple phenotype alterations, although seizure susceptibility evaluated by the bang-sensitivity assay revealed no consistent phenotype [ 195 ].…”
Section: Drosophila Epilepsy Modelsmentioning
confidence: 99%